2019
DOI: 10.1016/j.jhepr.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Ascites control by TIPS is more successful in patients with a lower paracentesis frequency and is associated with improved survival

Abstract: Cohort of 128 patients with refractory ascites TIPS Ascites control (95/128) Persistent ascites (33/128) Effect of persistent ascites on transplant-free survival Conclusion: ConsiderTIPS "early" in ascitic decompensation Ascites control is associated with transplant-free survival Ascites control by TIPS is more successful in patients with a lower paracentesis frequency and associated with improved survival Rik factors for persistent ascites:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
7
21
0
Order By: Relevance
“…In our cohort, most patients (80%) had more than 4 LVPs prior to allocation to TIPS, suggesting them more advanced in their liver disease progression. Thus, the mortality in our cohort is higher than in recent RCTs although similar to recent observational cohorts (35,65). However, the results of this study may encourage larger prospective multicenter studies.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 79%
“…In our cohort, most patients (80%) had more than 4 LVPs prior to allocation to TIPS, suggesting them more advanced in their liver disease progression. Thus, the mortality in our cohort is higher than in recent RCTs although similar to recent observational cohorts (35,65). However, the results of this study may encourage larger prospective multicenter studies.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 79%
“…Development of ascites is a poor prognostic factor in patients with cirrhosis, with a 1- and 2–year mortality of about 40 and 50%, respectively, and a median survival of 6 months once it becomes refractory to treatment [9]. In our population, TIPS placement was effective for refractory ascites, with response in 78.8% ( n = 26) of patients (33.3% achieving partial and 45.5% complete response), as seen in other reports [22, 30]. In our study, patients in whom ascites control failed were found to have significantly lower levels of baseline albumin, which is in line with the role of albumin in the pathophysiology of ascites [31].…”
Section: Discussionsupporting
confidence: 82%
“…However, subgroup analyses performed on the pooled data of these RCTs showed that TIPS significantly improved TFS regardless of whether recurrent ascites patients were included or not in the trials[ 89 ]. A recent single-center retrospective study of 128 patients showed that placement of TIPS in patients with lower LVP frequency and creatinine levels is associated with superior ascites control[ 103 ]. Similar findings were reported by a prospective RCT comparing TIPS to LVP in patients with recurrent ascites and a limited LVP frequency, which demonstrated benefits in ascites control and survival in TIPS-treated patients but no difference in HE between the two groups[ 92 ].…”
Section: Ascitesmentioning
confidence: 99%